Deformation and Fracturing Behaviors of Sandstone Disc Containing a Circular Inclusion under Diametrical Compression: Insights from Integrated SG and DIC Experiments - Nie, Rongshan; Wu, Qiuhong; Chu, Zhaofei; Weng, Lei (Shock and Vibration, 2023)
Weak inclusions play a significant role in regulating the deformation and fracturing behavior of rock masses. In this study, sandstone specimens filled with circular inclusions were subjected to diametrical compression until failure. The local strain concentration intensity and cracking process at the rock-inclusion interface were specifically investigated using the integrated strain gauge (SG) and digital image correlation (DIC) techniques. The experimental results reveal that the presence of inclusions introduces more complex deformation and fracturing behaviors in the infilled sandstone specimens. The stiffness of the infilled sandstones, with either low-strength or high-strength inclusions, initially increases and then decreases as the inclusion diameter increases. The effective load-carrying capacity of the infilled sandstone is influenced by the competing effects of inclusion enhancement and hole weakening. Moreover, a more pronounced strain concentration occurs at the inclusion boundary when the inclusion diameter is larger and the inclusion strength is lower. The crack mode in the infilled red sandstone is independent of the strength of the inclusion. For larger hole diameters, fracture planes form along the compression line, whereas interfacial debonding occurs in red sandstone with smaller hole diameters. Finally, the stress distribution characteristics along the loaded diameter and transverse diameter were analyzed using elastic finite element analyses, which can well explain the cracking mechanism of the infilled disc specimens.